SAVE: Audit System for Paperless Electronic Voting - Ferreira, Vanin Alves (Companion Proceedings of the Brazilian Symposium on Cybersecurity (SBSeg); 2025: Companion Proceedings of the 25th Brazilian Symposium on CybersecurityDO - 10.5753/sbseg_estendido.2025.14032, 2025)
The use of electronic voting machines has brought significant improvements to the Brazilian electoral process by eliminating fraud and issues associated with paper-based voting. However, the lack of mechanisms for independent auditing has raised concerns about the system's reliability and transparency, both within civil society and the academic community. This paper proposes the Secure Audit System for Electronic Voting (SAVE), which enables the verification of election results without relying on the voting machine's software or paper records. SAVE generates auditable and accessible evidence, facilitating the participation of non-technical voters in result validation.